Spring-mediated distraction enterogenesis may alter the course of adaptation in porcine short bowel syndrome - Bautista, Geoanna M.; Dubrovsky, Genia; Sweeney, Nicolle K.; Solórzano-Vargas, R.S.; Tancredi, Daniel J.; Lewis, Michael; Stelzner, Mattias; Martín, Martín G.; Dunn, James C.Y. (Frontiers in Gastroenterology, 2024)
Severe forms of short bowel syndrome (SBS) resulting in chronic intestinal failure (IF) have limited therapeutic options, all of which are associated with significant morbidities. Spring-mediated distraction enterogenesis (SMDE) uses an intraluminal self-expanding spring to generate mechanical force to induce intestinal stretching and sustained axial growth, providing a promising novel approach for patients with SBS. Previous studies have established this method to be safe and effective in small and large animal models. Here, we demonstrate the successful and reproducible implementation of SMDE in a large animal SBS model, providing the foundation for this novel method to be clinically utilized. In this study, juvenile mini-Yucatan pigs with 75% of their small intestine resected had intraluminal springs placed after an initial adaptive period. SMDE segments were then directly compared to the control region of the intestine undergoing normal adaptive responses to resection. While the initial histologic adaptive response observed following resection was attenuated after a month, the SMDE segments instead augmented these adaptive changes. Specifically, intestinal length increased 2-fold in SMDE segments, and the widths of the epithelial, muscularis, and serosal layers were enhanced in SMDE compared with control segments of the same animal. This data suggests that morphologic intestinal adaptation may be enhanced with SMDE in the setting of SBS. For the first time, we demonstrate SMDE-induced changes in a large animal model in the setting of prior intestinal resection, making SMDE a viable and novel approach for SBS to be explored further.